Pilonidal disease: comparative analysis of leading professional organizations clinical guidelines - Byk , Pavlo; Bilіanskyi , Leonid; Burka , Anatolii (The Ukrainian Scientific Medical Youth Journal, 2024)
pilonidal disease is an inflammatory disease that is most often localized in the sacrococcygeal area and is characterized by the formation of a cyst or abscess with the possible secondary formation of fistulas. Pilonidal disease is a fairly common disease, according to individual studies, the incidence ranges from 26 cases per 100,000 people (USA) to 48 per 100,000 people (Germany). Men are three times more likely to suffer than women. Most often, the disease manifests itself between the ages of 18 and 30. The risk factors for developing the disease are: excess weight, increased hair growth, chronic trauma to the sacrococcygeal area and anatomical features of the gluteal cleft (its shape, depth, configuration). The occurrence and development of the disease in persons of working age often leads to a sharp decrease in work capacity and quality of life. There is still no single, generally accepted classification of pilonidal disease in the world. Today, there are 3 clinical guidelines created by professional associations (USA, Germany, Italy), based on the principles of evidence-based medicine. The purpose of the study is to perform a comparative analysis of the main points of the clinical guidelines of leading professional organizations (German National Guideline on the management of pilonidal disease, The American Society of Colon and Rectal Surgeons' Clinical Practice Guidelines for the Management of Pilonidal Disease, Consensus statement of the Italian society of colorectal surgery: management and treatment of pilonidal disease) regarding the clinical-diagnostic approach and the choice of optimal treatment tactics for patients with certain forms of pilonidal disease. In the study, a review and comparative analysis of literary sources from the scientific databases of medical literature PubMed Central (U.S. National Institutes of Health's National Library of Medicine), ScienceDirect (Elsevier publishing house), Wiley online library, Springer Link, Cochrane library, materials of the 3rd International Pilonidal Conference ( 2023, Copenhagen, Denmark) and clinical guidelines of specialized organizations of the USA, Germany and Italy. The following issues of diagnosis and treatment of diseases are selected for comparative analysis: choice of prevention method and non-surgical procedures that reduce the risk of disease recurrence; choice of treatment method and assessment of its necessity for asymptomatic pilonidal cysts; the choice of a surgical method of treatment for symptomatic pilonidal cysts; the choice of a method of surgical treatment for a recurrent form of PC. According to the performed analysis, it can be concluded that the diagnostic and therapeutic strategies reflected in the clinical guidelines are based on the evidence base and the analysis of research data conducted in the field of treatment of pilonidal disease, which leads to the existence of an essential correlation between the recommendations related to the choice of a method of prevention and non-surgical procedures that reduce the risk of recurrence of the disease, the method of treatment and assessment of its necessity for the asymptomatic form of the disease, methods of surgical treatment of the recurrent form of the disease. There are differences between clinical guidelines due to varying general consensus structures and main questions chosen to form a list of general provisions.